2021
DOI: 10.1016/j.carrev.2020.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of COVID-19 Related Myocarditis: Insights on Management and Outcome

Abstract: Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also referred to as COVID-19, was declared a pandemic by the World Health Organization in March 2020. The manifestations of COVID-19 are widely variable and range from asymptomatic infection to multi-organ failure and death. Like other viral illnesses, acute myocarditis has been reported to be associated with COVID-19 infection. However, guidelines for the diagnosis of COVID-19 myocarditis have not been established. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
236
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(257 citation statements)
references
References 47 publications
6
236
0
15
Order By: Relevance
“…Sawalha et al [ 15 ] identified a total of 14 cases with myocarditis/myopericarditis believed to have occurred secondary to COVID-19 infection from December 1st 2019 to June 30th 2020. There was a male predominance (58%), with the median age of 50.4 years.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sawalha et al [ 15 ] identified a total of 14 cases with myocarditis/myopericarditis believed to have occurred secondary to COVID-19 infection from December 1st 2019 to June 30th 2020. There was a male predominance (58%), with the median age of 50.4 years.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the diagnostic work-up for coronary artery disease, the report of Sawalha et al [ 15 ] included CCT (17% of cases) and invasive coronary angiography (25% of cases). No patients were found to have any obstructive coronary disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, COVID-19 has demonstrated deleterious effects on the cardiovascular system in patients with and without preexisting cardiovascular disease. Cardiovascular involvement has been shown to be a negative prognostic factor in these patients [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. Furthermore, the pandemic appeared to decrease ST-elevation myocardial infarction (STEMI) presentations in the initial phases globally [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%